Review of The reparative effects of human rights trials. Lessons from Argentina - van Drunen, Saskia (European Review of Latin American and Caribbean Studies, 2021)
The reparative effects of human rights trials. Lessons from Argentina, by Rosario Figari Layús, Routledge, 2018